Investigations in the field of Neuropsychology: peculiar aspects of attention-deficit with hyperactivity disorder (Research, Society and Development, 2021)
Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent comorbidities, affecting children, adolescents, and adults. Its multifactorial condition represents a challenge to close the diagnosis. In this sense, neuropsychological assessment has an eminently clinical approach and should consider both the neurobiological aspects of the disorder, as well as the life history of individuals. From this perspective, this paper aims to present a theoretical reflection on the historical aspects of ADHD, its causes, and the impacts on biopsychosocial development. It also seeks to highlight the relevance of neuropsychological assessment in the diagnosis of the disorder. This is a literature review study, carried out through the analysis of national scientific papers indexed in different databases. The results show that ADHD has been discussed in a context of multiple approaches, whose purpose has been, on the one hand, to seek answers for a problem that has not yet been fully clarified. It can be concluded that one should seek contributions and strategies for more assertive evaluations and interventions that aim to improve the socio-affective, family, and educational condition.